Project Acceleration Analysis Using the Time Cost Trade Off Method in the Phase II Construction of the Serayu Pegalongan – Mandirancan River Bridge, Banyumas Regency - Manuputty, Ranu Saputra Dewa; Prajitno, Achmad Faiz Hadi (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
The Serayu River Bridge is a bridge that connects Pegalongan Village with Mandirancan Village, Banyumas Regency, Central Java Province. This bridge has a total length of 140 meters divided into three spans using steel and reinforced concrete structures and has a road width of 8 meters. The implementation of the Serayu River Bridge phase II project has a planned duration of 150 calendar days from July 26, 2021, to December 22, 2021. However, in its implementation, there was a delay of 30 working days from the initial plan. The delay occurred because October had entered the rainy season and several other causes of delay. This study aimed to analyze the acceleration of the Serayu River Bridge phase II project to get the optimum time and cost. Acceleration was carried out by Time Cost Trade Off (TCTO) analysis based on conditions in the field. The alternative used was by adding work shifts and labor. Thus, with the acceleration analysis using these two alternatives, it is expected to produce a more optimum alternative in the project implementation if it experiences delays in terms of time and cost. After the acceleration analysis, it was found that the acceleration alternative with the addition of work shifts could be accelerated from 30 working days to 120 working days (down 20.00%). The project’s total cost, which initially amounted to IDR 10.794.871.204 to IDR 10.766.272.352, then there was a difference of IDR 28.598.851 from the project implementation before acceleration (down 0.26%). Meanwhile, the acceleration alternative with additional labor could be accelerated from 12 working days to 138 working days (down 8.00%). The total project cost, which initially amounted to IDR 10.794.871.204 to IDR 10.763.795.717, then there was a difference of IDR 31.075.486 from the project implementation before acceleration (down 0.29%).